Strategi Tokoh Agama Dalam Memakmurkan Masjid Muhajirin di Desa Kayu Ara Batu Kecamatan Muara Belida - Risma Wati; Candra Darmawan (Social Science and Contemporary Issues Journal, 2023)
This research is entitled "Strategy of Religious Leaders in Prospering the Muhajirin Mosque in Kayu Ara Batu Village, Muara Belida District, Muara Enim Regency. strategy of religious leaders in prospering the Muhajirin mosque in Kayu Ara Batu village, Muara Belida sub-district, Muara Enim district. The type of research used is field research and a descriptive qualitative approach. This research uses primary data sources and secondary data sources, while data analysis is in research This study uses observation, interviews, and documentation. The location of Kayu Ara Batu village, Muara Belida sub-district, Muara Enim district. The data analysis technique in this study is descriptive qualitative, by means of data reduction, data presentation, and drawing conclusions. The theory used is strategic management according to Achmad Djueni Kadmasasmita. The results of this study are the strategies of religious leaders in the village of Kayu Ara Batu, Muara Belida District, Muara Enim Regency. Divided into 3 strategies Growing a sense of belonging to the mosque, Formulating Activity Programs, Completing Mosque Facilities. While there are 3 inhibiting factors, namely work factors, road factors, time factors. However, in prospering this mosque there are several problems such as the mosque management is not active so the mosque is not well taken care of, lack of mosque facilities, there is no prayer barrier between male and female congregations so that worshipers come to the mosque feeling uncomfortable, people are still busy with their work each so that they are negligent in carrying out congregational prayers at the mosque           ABSTRACT: This research is entitled "Strategy of Religious Leaders in Prospering the Muhajirin Mosque in Kayu Ara Batu Village, Muara Belida District, Muara Enim Regency. strategy of religious leaders in prospering the Muhajirin mosque in Kayu Ara Batu village, Muara Belida sub-district, Muara Enim district. The type of research used is field research and a descriptive qualitative approach. This research uses primary data sources and secondary data sources, while data analysis is in research This study uses observation, interviews, and documentation. The location of Kayu Ara Batu village, Muara Belida sub-district, Muara Enim district. The data analysis technique in this study is descriptive qualitative, by means of data reduction, data presentation, and drawing conclusions. The theory used is strategic management according to Achmad Djueni Kadmasasmita. The results of this study are the strategies of religious leaders in the village of Kayu Ara Batu, Muara Belida District, Muara Enim Regency. Divided into 3 strategies Growing a sense of belonging to the mosque, Formulating Activity Programs, Completing Mosque Facilities. While there are 3 inhibiting factors, namely work factors, road factors, time factors. However, in prospering this mosque there are several problems such as the mosque management is not active so the mosque is not well taken care of, lack of mosque facilities, there is no prayer barrier between male and female congregations so that worshipers come to the mosque feeling uncomfortable, people are still busy with their work each so that they are negligent in carrying out congregational prayers at the mosque.   KEYWORDS: Strategy, Religious Leader, Muhajirin Mosque. Submitted:Revised:Accepted:     ABSTRACT:This research is entitled "Strategy of Religious Leaders in Prospering the Muhajirin Mosque in Kayu Ara Batu Village, Muara Belida District, Muara Enim Regency. strategy of religious leaders in prospering the Muhajirin mosque in Kayu Ara Batu village, Muara Belida sub-district, Muara Enim district. The type of research used is field research and a descriptive qualitative approach. This research uses primary data sources and secondary data sources, while data analysis is in research This study uses observation, interviews, and documentation. The location of Kayu Ara Batu village, Muara Belida sub-district, Muara Enim district. The data analysis technique in this study is descriptive qualitative, by means of data reduction, data presentation, and drawing conclusions. The theory used is strategic management according to Achmad Djueni Kadmasasmita. The results of this study are the strategies of religious leaders in the village of Kayu Ara Batu, Muara Belida District, Muara Enim Regency. Divided into 3 strategies Growing a sense of belonging to the mosque, Formulating Activity Programs, Completing Mosque Facilities. While there are 3 inhibiting factors, namely work factors, road factors, time factors. However, in prospering this mosque there are several problems such as the mosque management is not active so the mosque is not well taken care of, lack of mosque facilities, there is no prayer barrier between male and female congregations so that worshipers come to the mosque feeling uncomfortable, people are still busy with their work each so that they are negligent in carrying out congregational prayers at the mosque.